Heat Transfer Enhancement Using Helical Pipes - Helal Zgayer, Ajaj (Anbar Journal of Engineering Sciences, 2012)
The enhancement of laminar forced convection inside helical pipes is studied numerically and compared with plain pipes. The study is achieved numerically using the (Fluent-CFD 6.3.26) software program for solving the governing equations. The heat transfer coefficient and friction coefficient are calculated using the enhancement technique and compared with the plain tube. In this research the factors that affect the enhancement technique using helical pipes are studied, these factors are the ratio of (pitch /pipe length) (SL), Reynolds number and the heat flux applied to the external surface of the pipe. The results showed that there is an increasing in the heat transfer coefficient is related to the decreasing of (SL), increasing of Reynolds number and heat flux. The performance of the helical pipes is evaluated depending on the calculation of (Enhancement ratio), and it’s found that the enhancement ratio increases as Reynolds number increases and (SL) decreases. It is found that the best enhancement ratio was (200%) at (SR=0.05), (Re=2000),(Heat flux=3000W/m2).The results are compared with the literature and there is a good agreement.